Assessment of levan production from sucrose by Zymomonas mobilis CCT 4494 - Ferreira, Juliana [UNESP]; Santos, Vidiany Aparecida Queiroz; Calegari, Gabrielle Cristina; Cruz, Crispin Humberto Garcia [UNESP] (Instituto de Quimica - Univ. Federal do Mato Grosso do Sul, 2019)
Levan is a polymer composed of fructose units linked by β(2→6) glycosidic bonds. It can be found in many plants and microbial products, and it has many applications in different industrial fields, such as foods and pharmaceuticals. The aim of this study was to analyze levan production from sucrose by Zymomonas mobilis CCT 4494. A 24-1 fractional design was carried out to evaluate the effects of pH, temperature, sucrose concentration and time. The statistical analysis (p<0.10) showed that the effect of the sucrose concentration was the most important influence on the levan concentration followed by the effect of the temperature. The best levan biosynthesis condition was at 25 ºC, with initial pH value of 4.5, 250 g L-1 of sucrose concentration during 72 h of fermentation. Furthermore, highest levan production was 7.6 g L-1, at 25 °C with sucrose concentration of 250 g L-1.
Keywords: Batch fermentation; Biopolymer; Exopolysaccharide; Statistical methodology